MENAKAR KONSEPSI KHILAFAH - Musa Arifin (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
The word "khilafah" returned to public opinion after the government dissolved Hizb ut-Tahrir Indonesia as an organization that had a vision and mission to uphold the Caliphate. The government seems to assume that the khilafah system is not an Islamic teaching.